Factors Influencing Internet Financial Reporting Quality: Audit Opinion as a Moderator - Wahyuni, Fitri; Arpris Pangestu, Arya (SEAN Institute, 2024)
This study aims to assess how debt financing ratios, the size of local government, and financial performance collectively influence the quality of Internet financial reporting in provincial regional governments in Indonesia. Additionally, the study considers audit opinion as a moderating variable. The research is focused on the provincial regional governments of Indonesia, with a sample size of 81 entities selected through purposive sampling. For hypothesis testing, the study employs multiple linear regression with Moderated Regression Analysis (MRA). The collected data undergoes classical assumption testing before the hypothesis is tested, utilizing the SPSS 22.0 tool. The results indicate that Financial Performance has a positive impact on the quality of Internet financial reporting. In contrast, Debt Financing Ratios and the size of the local government do not significantly affect the quality of Internet financial reporting. The moderation role of audit opinion is highlighted, showing a significant positive effect in moderating the relationship between financial performance and the quality of Internet financial reporting. Conversely, audit opinion exhibits a significant negative effect in moderating the relationship between Debt Financing Ratio, regional government size, and the quality of Internet financial reporting.